Resolution of Consumer Disputes that are Certain, Equitable, Effective and Efficient in South Sumatra - Rosmawati, Rosmawati; Ng, H Mashaal; Syamsuddin, H (Law Research Review Quarterly, 2016)
Consumer disputes often occur in the community in South Sumatra Province. Currently consumers must be smart in facing the era of globalization and the free market which results in positive and negative things that can happen to consumers due to the large number of products that will not necessarily meet the quality standards set by the rules of the law. The purpose of this study is to analyze how consumer dispute resolution is, and explain how consumer dispute resolution through BPSK and develop a consumer dispute resolution model in South Sumatra. The method used is through an empirical legal approach. The results of the research that can be concluded are: (1) Settlement of consumer disputes that is certain, fair, effective and efficient in South Sumatra has not gone well, this is due to the lack of information on the existence of BPSK to the public and the community itself seems to be of a stupid period (no concern, no side another lack of government support for violations by producers) so as not to create a deterrent effect for business actors (producers); and (2) a model for resolving consumer disputes that is certain, effective and efficient is a form of regional regulation of the South Sumatra province that includes BPSK in the regions but it is unfortunate that the existence of BPSK is not yet known by the people of South Sumatra, whereas the settlement through BPSK is fairly fair, satisfying all parties , both consumers and producers.